Elemental imaging at the nanoscale: NanoSIMS and complementary techniques for element localisation in plants. - Moore, K; Lombi, E; Zhao, F; Grovenor, C (2012)
The ability to locate and quantify elemental distributions in plants is crucial to understanding plant metabolisms, the mechanisms of uptake and transport of minerals and how plants cope with toxic elements or elemental deficiencies. High-resolution secondary ion mass spectrometry (SIMS) is emerging as an important technique for the analysis of biological material at the subcellular scale. This article reviews recent work using the CAMECA NanoSIMS to determine elemental distributions in plants. The NanoSIMS is able to map elemental distributions at high resolution, down to 50 nm, and can detect very low concentrations (milligrams per kilogram) for some elements. It is also capable of mapping almost all elements in the periodic table (from hydrogen to uranium) and can distinguish between stable isotopes, which allows the design of tracer experiments. In this review, particular focus is placed upon studying the same or similar specimens with both the NanoSIMS and a wide range of complementary techniques, showing how the advantages of each technique can be combined to provide a fuller data set to address complex scientific questions. Techniques covered include optical microscopy, synchrotron techniques, including X-ray fluorescence and X-ray absorption spectroscopy, transmission electron microscopy, electron probe microanalysis, particle-induced X-ray emission and inductively coupled plasma mass spectrometry. Some of the challenges associated with sample preparation of plant material for SIMS analysis, the artefacts and limitations of the technique and future trends are also discussed.